Development of Application-Based Interactive Learning Media in Automotive Engineering - Choyrul Anwar; Andi Maga Umara; Muhammad Nurtanto; Valiant Lukad Perdana Sutrisno; Fadly Nendra; Rusdi Febriyanto (Malikussaleh University, Aceh, Indonesia, 2025)
Learning media significantly impacts the effectiveness of the learning process. The automotive industry is experiencing rapid development, resulting in a high demand for technicians with expertise in the automotive field. The purpose of this study was to test the development of Smart Apps Creator (SAC) to create interactive learning resources for Engine Management Systems (EMS). This research and development (RD) project used the ADDIE development approach. Five subject matter experts and five media specialists comprised an expert assessment group that validated and evaluated the media to ensure its feasibility. In addition, 62 students reviewed the learning materials as users of the application. The media specialists' evaluation of the feasibility of the learning media construction resulted in a score of 4.02, which is considered practical. The subject matter experts' evaluation of the feasibility of the learning media material resulted in a score of 4.15, which is considered practical. The students' evaluation of the acceptance of the learning media as users resulted in a score of 4.07, which is classified as practical. Meanwhile, the application implementation in the learning process proved to increase learning success among students who used the program development. All things considered, the findings of this study can be used as evidence that application-based learning materials are worthy of widespread use, which will further improve teaching standards. Furthermore, vocational teachers must innovate in developing learning media by utilizing and integrating technology into the process. The creation of such media is necessary in the 21st century to provide easily accessible and understandable learning materials so that students can effectively absorb the information.